PAULO FREIRE'S PERSPECTIVE ON EDUCATION: THE NEIGHBORHOOD OF THE REALITY OF INDONESIAN EDUCATION - Asman Asman (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2023)
Education is something that is very basic in human life. This study aims to analyze the educational perspective of Paulo Freire in light of the reality of Indonesian education. Which, if we observe the style of Indonesian education, is still like what was used in the time of Paulo Freire with the model of the Bank style. This research is a literature study with a qualitative approach. The data source for this research is various literature, both from books and journals related to the educational perspective of Paulo Freire. The results of this study indicate that Indonesian education still uses the banking model, as stated by Paulo Freire. Then there are many educational theories and education systems that buy up styles or so many subjects that Indonesian education does not progress. As well as a lack of understanding of the nature of education, which also makes the teacher unable to see the hidden potential in students.